Massive open online courses: history, typology, perspectives - K. L. Bugaychuk (Высшее образование в России, 2022)
The article explores the phenomenon of emergence in the Internet of massive open online courses (MOOC). The author considers the main types of MOOC (cMOOC, task-based MOOC,xMOOC), their applicability at universities, advantages and disadvantages, prospects for further development.